Managing in clearing garden type 1 with Sabr min al Iman - Mhd. Sarif, Suhaimi; Zainudin, Dolhadi (International Islamic University Malaysia, 2019)
This report describes the clearing of vegetable garden Type 1 with Sabr min al Iman. Type 1 Garden denotes the first level of clearing. The Sabr min al Iman means, the doing with full level of faith and passion in clearing the garden.